Ethical decision making behind the wheel – A driving simulator study. (May 2020) - Samuel, Siby; Yahoodik, Sarah; Yamani, Yusuke; Valluru, Krishna; Fisher, Donald L.
Abstract: Over the past several years, there has been considerable debate surrounding ethical decision making in situations resulting in inevitable casualties. Given enough time and all other things being equal, studies show that drivers will typically decide to strike the fewest number of pedestrians in scenarios where there is a choice between striking several versus one or no pedestrians. However, it is unclear whether drivers behave similarly under situations of time pressure. In our experiment in a driving simulator, 32 drivers were given up to 2 s to decide which group of pedestrians to avoid among groups of larger (5) or smaller (≤1) number of pedestrians. Our findings suggest that while people frequently choose utilitarian decisions in the typical, abstract manifestations of the Trolley Problems, drivers can fail to make utilitarian decisions in simulated driving environments under a restricted period of time representative of the time they would have to make the same decision in the real world (2 s). Analysis of eye movement data shows that drivers are less likely to glance at left and right sides of crosswalks under situations of time duress. Our results raise critical engineering and ethical questions. From a cognitive engineering standpoint, we need to know how long at minimum a driver needs to make simple, moral decisions in different scenarios. From an ethical standpoint, we may need to evaluate whether automated vehicle algorithms can aid decision making on our behalf when there is not enough time for a driver to make a moral decision. Highlights: People overwhelmingly prefer utilitarian outcomes and decisions when faced with abstract hypothetical ethical decisions. Only 43% of participants maneuvered their car towards a single pedestrian to avoid hitting a group of pedestrians. Only 63% of participants maneuvered their car towards an area with no pedestrians to avoid hitting a group of pedestrians. Two seconds is too short of time for drivers to make complex decisions involving ethical reasoning.